2022
DOI: 10.4240/wjgs.v14.i9.976
|View full text |Cite
|
Sign up to set email alerts
|

Feasible management of median arcuate ligament syndrome in orthotopic liver transplantation recipients

Abstract: BACKGROUND In orthotopic liver transplantation (OLT) recipients, median arcuate ligament syndrome (MALS) is considered a risk factor for hepatic arterial thrombosis (HAT), which is dreadful for OLT recipients. Different alternative surgical procedures have been proposed to overcome the impact of MALS on transplantation, but clinical evidence is still scarce. AIM To evaluate the feasible surgical management of MALS to reduce complications in OLT patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Another important consideration about MALS occurs in the case of orthotopic liver transplantation. In these patients, MALS is considered a predisposing factor for hepatic artery thrombosis, due to the hemodynamic compromises in the hepatic artery[ 19 ]. Specifically, the compression from the median arcuate ligament is responsible for a reduction of blood velocities in the hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important consideration about MALS occurs in the case of orthotopic liver transplantation. In these patients, MALS is considered a predisposing factor for hepatic artery thrombosis, due to the hemodynamic compromises in the hepatic artery[ 19 ]. Specifically, the compression from the median arcuate ligament is responsible for a reduction of blood velocities in the hepatic artery.…”
Section: Discussionmentioning
confidence: 99%
“…This vascular compromise may contribute to reduced blood supply to the liver graft, biliary complications, and hepatic artery thrombosis[ 20 ]. In a recent retrospective study regarding patients receiving orthotopic liver transplantation, the presence of MALS dictated different management for the graft to be preserved and the procedure to be a success[ 19 ]. According to Li et al [ 19 ], if flow from the hepatic artery is found to be reduced, the gastroduodenal arteries and the collateral branches should be preserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various open approaches to arterial reconstruction have been described during PD including jejunal artery-to-GDA, middle colic artery-to-GDA, celiac trunk to hepatic artery, aorto-hepatic artery, reimplantation of the celiac trunk, and bypass grafting [9,[48][49][50]. The release of MAL in OLT patients with portal hypertension carries significant risk due to the presence of gastroesophageal varices and extensive collateral blood flow between the celiac trunk and SMA [4,31,51]. In some patients with extensive collateral supplies, preservation of collateral arteries and GDA without performing MAL release may provide adequate blood flow in the hepatic artery [51].…”
Section: Management Of Median Arcuate Ligament Syndrome and Our Exper...mentioning
confidence: 99%
“…The release of MAL in OLT patients with portal hypertension carries significant risk due to the presence of gastroesophageal varices and extensive collateral blood flow between the celiac trunk and SMA [4,31,51]. In some patients with extensive collateral supplies, preservation of collateral arteries and GDA without performing MAL release may provide adequate blood flow in the hepatic artery [51]. However, if surgical release fails to restore hepatic artery flow, options for hepatic artery reconstruction will be limited.…”
Section: Management Of Median Arcuate Ligament Syndrome and Our Exper...mentioning
confidence: 99%